The role of virtual grid to increase contrast-to-noise ratio in thorax radiography - Liscyaningsih, Ike Ade Nur; Mahanani, Ayu; Istiqomah, Anisa Nur; Ma’ruf, Muhammad Alwan (Universitas 'Aisyiyah Yogyakarta, 2024)
Thorax is a dense object, necessitating the use of a grid. However, hospitals use physical grids, which have drawbacks such as increased doses, appearance of artifacts, and a lack of ergonomics. To address these issues, virtual grid technology has been developed. This study aims to describe the thorax radiographic examination using a virtual grid and to compare the CNR of thorax radiographs using physical and virtual grids. This study uses a mixed-methods experimental, conducted at the Radiology Laboratory of 'Aisyiyah University Yogyakarta from November 2023 to May 2024. Data were collected through observation and experiments with a thorax phantom, physical and virtual grids, and CNR measurements at 5 points on images using ImageJ. The sample is thorax radiographic was tested in 5 trials each. Data analysis was performed using the paired samples T-Test. The results of thorax radiographic imaging using the virtual grid showed that after exposure, the image appeared on the monitor. Activating the virtual grid feature (ON) with 8:1 grid ratio, CNR were measured at each ROI. CNR with the physical grid were average of 27.22. With the virtual grid, the CNR were average of 40.81. These results indicate that the image quality using the virtual grid is superior. Statistical analysis showed a significant difference, with a p-value of 0.018. These findings suggest that the virtual grid not only improves image quality but also enhances workflow efficiency and operational ergonomics examinations. Future studies should explore the broader applicability of virtual grid technology in different radiographic modalities.